Ekstradisi Terpidana Kasus Korupsi Dalam Rangka Penegakan Hukum Tindak Pidana Korupsi (Lex Jurnalica, 2012)
AbstractVarious problems or challenges faced by law enforcement agencies in eradicating corruption. Not a few too many of the perpetrators of corruption in both the status of the suspect, accused or convicts who fled abroad. The condition is aggravated by assets also brought corruption proceeds abroad. Therefore, in order to be able to bring back the perpetrators of corruption who fled abroad including assets proceeds of corruption that brought the law enforcement officers need to use the mechanism of